Seasonal and periodic rhythmicity of respiratory infections in small ruminants. Issue 7 (2nd October 2020) - Muheet,; Malik, Hamid Ullah; Parray, Oveas Rafiq; Bhat, Riyaz Ahmed; Yatoo, Mohd Iqbal
ABSTRACT: In this study, seasonal and periodic rhythmicity of various respiratory infections in small ruminants were studied. A total of 380 animals (200 sheep, 180 goats) were screened in winter and summer seasons for Mycoplasma, bacteria, and virus (Morbilivirus) infections. Agglutination test for Mycoplasma, competitive enzyme-linked immunosorbent assay for Mycoplasma capricolum subspecies capripneumonia (Mccp), culture for Pasteurella, and sandwich ELISA for morbillivirus, was used. Seasonal prevalence was 7% and 5% of mycoplasmosis, 7% and 8.33% of pasteurellosis and 24% and 28.89% of PPR in sheep and goat in winter and 4%, 6%, 17.5% and 3.3%, 6.6%, 16.11% in summer, respectively. Periodicity noted was PPR infection followed by mycoplasmosis and pasteurellosis. Young ones were found to be more susceptible followed by older ones than adults. Females were found to be more affected than males (29.5%–30%). Positive correlation was found between seropositivity and season, age, and gender. In conclusion, respiratory infections have seasonal occurrence with more cases occurring during winter and periodic rhythmicity includes PPR followed by mycoplasmosis and pasteurellosis. Hence, this study helps in establishing the seasonal occurrence, periodic rhythmicity, and age and gender-wise prevalence of respiratory infections in small ruminants that can be exploited for disease management and prevention strategies.